PENGGUNAAN METODE NEW INFORMATION ECONOMICS UNTUK MENINGKATKAN KINERJA USAHA MELALUI SISTEM INFORMASI - Hudiarto Hudiarto; Indra Indra; Ervien Ervien; Dhanny Cahyadi (Bina Nusantara University, 2008)
PFI is a financing institution (multifinance) that since 2004, focusing on consumer finance who want to own a motorcycle. PFI has been utilizing the information system and technology (IS/IT) in the overall business processes both on the system application is currently running (lights on), infrastructure, services, management and application projects planning. The research objective was to give a clear picture to the management about benefits and impacts that can be obtained from the IS/ IT investment both lights on and appplication projects. Researchers propose to analyze the lights on and the application projects is using the New Information Economics (NIE) and uses four of the NIE five practices that are Demand/Supply Planning, Innovation, Prioritization, and Alignment. The research result is an IS/IT strategy investment in the lights on, fulfilling the needs of the IS/IT, the creation of new innovations, as well as priority application projects based on the company’s strategic direction. Conclusions obtained are the company can find out where the lights on should be developed, improved, or even ignored. And to knowing which application projects should take precedence, so the company can allocate future resources to the lights on and the right application projects that supports corporate strategic direction.Keywords: lights on, application projects, New Information Economics (NIE)